Peningkatan Kemahiran Advokat dalam Registrasi Putusan Arbitrase Asing di Indonesia - Sidik, Jafar; Priyanto, Imam Jahrudin; Rozali, Asep; Orlov, Oleg (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2023)
Indonesia is a country that has ratified the 1981 New York Convention through Presidential Decree Number 34 of 1981, so that foreign or international arbitral awards can be implemented in Indonesia after being registered by the arbitrator or his proxy at the Central Jakarta District Court. Advocates can be appointed as attorney for arbitrators to register international arbitral awards. However, currently there are still few Indonesian advocates who understand the registration and implementation of international arbitral awards in Indonesia. We organize national seminars on arbitration socialization or training, particularly on the registration of foreign arbitral awards. This socialization implementation was designed using a partner participation approach as socialization and training participants. After attending the outreach seminar, the advocates understood and mastered the process of registering international arbitral awards in Indonesia.